Attitudes and Acceptance Towards Artificial Intelligence in Medical Care. - Holzner, Dana; Apfelbacher, Timo; Rödle, Wolfgang; Schüttler, Christina; Prokosch, Hans-Ulrich; Mikolajczyk, Rafael; Negash, Sarah; Kartschmit, Nadja; Manuilova, Iryna; Buch, Charlotte; Gundlack, Jana; Christoph, Jan (Studies in health technology and informatics, 2022)
BACKGROUND: Artificial intelligence (AI) in medicine is a very topical issue. As far as the attitudes and perspectives of the different stakeholders in healthcare are concerned, there is still much to be explored. OBJECTIVE: Our aim was to determine attitudes and aspects towards acceptance of AI applications from the perspective of physicians in university hospitals. METHODS: We conducted individual exploratory expert interviews. Low fidelity mockups were used to show interviewees potential application areas of AI in clinical care. RESULTS: In principle, physicians are open to the use of AI in medical care. However, they are critical of some aspects such as data protection or the lack of explainability of the systems. CONCLUSION: Although some trends in attitudes e.g., on the challenges or benefits of using AI became clear, it is necessary to conduct further research as intended by the subsequent PEAK project.
EVALuna2:528248